Determination of Biofilm Formation and Antibiotic Susceptibility in Non-Fermentative Gram-Negative Bacteria - Dursun, Muhammed Fatih; Oner, Pinar; Toraman, Zülal Aşçı (My University, 2023)
Objective: This article aims to determine the biofilm production and antibiotic sensitivity in Non- Fermentative Gram-Negative (NFGN) bacteria isolated from various clinical samples. Materials and Methods: A total of 150 NFGN bacteria (Pseudomonas aeruginosa)(42), Acinetobacter baumannii (104), Burkholderia cepacia (4) defined in conventional methods and automated system of VITEK 2 (Biomerieux, France) isolated from 81 wounds, 29 urine, 12 sterile body fluids, 12 blood, 16 respiratory tract samples, which were sent to the Microbiology Laboratory of our hospital, were included in this study. Congo Red Agar (CRA), Standard Tube (ST), and Microplate (MP) methods were used to determine the biofilm formation. Results: 71(47.33%) of 150NFGN bacterial isolates were found to be biofilm positive according to the CRA method. 57(38%) of the isolates were found to be biofilm positive according to the ST method using crystal violet dye, and 61(40.7%) according to the MP method. 65(43.3%) of the isolates were detected as biofilm positive according to the ST method using safranine dye, and 83(55.3%) according to the MP method, respectively. It was determined that biofilm-positive A. baumannii strains showed resistance to amoxicillin-clavulanic acid 88.89% and trimethoprim- sulfamethoxazole 87.04%. It was determined that biofilm positive P. aeruginosa strains showed 82.86% resistance to amoxicillin-clavulanic acid and 85.72% to trimethoprim-sulfamethoxazole. It was revealed that B. cepacia isolates showed 100% resistantance to all antimicrobials except colistin and cefoperazone-sulbactam. Conclusions: The MP method, using safranine dye, which is shown as the gold standard test among the test methods performed for the determination of biofilm formation, was determined as the method with the highest biofilm positivity rate in our study.
Keywords: Mikrobiyoloji; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Tıbbi Laboratuar Teknolojisi